Is digitalization a source of innovation? Exploring the role of digital diffusion in SME innovation performance - Hassan Sohaib S.; Meisner Konrad; Krause Kevin; Bzhalava Levan; Moog Petra (United States, 2025)
Drawing on strategic management theory, this study examines the relationship between digitalization and innovation performance in small and medium-sized enterprises (SMEs). We hypothesize that SMEs with higher levels of digital diffusion have higher innovation performance, and that absorptive capacity moderates this relationship. To test this relationship, we use a sample of 1100 German SMEs from the Mannheim Innovation Panel of the Centre for European Economic Research. The results of the multinomial and multivariate probit estimations show that digital diffusion is a significant positive trigger of innovation in SMEs. We also find that absorptive capacity moderates the relationship between digital diffusion and innovation only in the case of product innovation and not for any other type of innovation. Finally, we discuss the implications of our study for research and practice.